An efficient medium-bandgap nonfullerene acceptor for organic solar cells. Issue 18 (22nd April 2020) - Liu, Qishi; Jin, Ke; Li, Wenting; Xiao, Zuo; Cheng, Ming; Yuan, Yongbo; Shi, Shengwei; Jin, Zhiwen; Hao, Feng; Yang, Shangfeng; Ding, Liming
Abstract : A medium-bandgap nonfullerene acceptor IBCT was developed, delivering 11.26% and 15.25% power conversion efficiencies in single-junction and tandem solar cells, respectively. Abstract : A medium-bandgap acceptor IBCT based on an 2-(1-oxo-1, 2-dihydro-3 H -benzo[ b ]cyclopenta[ d ]thiophen-3-ylidene)malononitrile end unit was developed. IBCT has an optical bandgap of 1.65 eV and afforded a power conversion efficiency of 11.26% and an open-circuit voltage of 1.02 V in single-junction organic solar cells when blending with a wide-bandgap copolymer donor L1. The L1:IBCT solar cell was further used as the front cell in tandem solar cells, yielding a 15.25% efficiency. IBCT is among the best medium-bandgap acceptors.